Nanomaterials-based Drug Delivery Approaches for Wound Healing - Girija, Aswathy R.; Balasubramanian, Sivakumar; Cowin, Allison J. (Current Pharmaceutical Design, 2022)
Wound healing is a complex and dynamic process that requires intricate synchronization between multiple cell types within appropriate extracellular microenvironment. Wound healing process involves four overlapping phases in a precisely regulated manner, consisting of hemostasis, inflammation, proliferation, and maturation. For an effective wound healing, all four phases must follow in a sequential pattern within a time frame. Several factors might interfere with one or more of these phases in healing process, thus causing improper or impaired wound healing resulting in non-healing chronic wounds. The complications associated with chronic non-healing wounds, along with the limitations of existing wound therapies, have led to the development and emergence of novel and innovative therapeutic interventions. Nanotechnology presents unique and alternative approaches to accelerate the healing of chronic wounds by the interaction of nanomaterials during different phases of wound healing. This review focuses on recent innovative nanotechnology-based strategies for wound healing and tissue regeneration based on nanomaterials, including nanoparticles, nanocomposites and scaffolds. The efficacy of the intrinsic therapeutic potential of nanomaterials (including silver, gold, zinc oxide, copper, cerium oxide, etc.) and the ability of nanomaterials as carriers (liposomes, hydrogels, polymeric nanomaterials, nanofibers) and therapeutic agents associated with wound-healing applications have also been addressed. The significance of these nanomaterial-based therapeutic interventions for wound healing needs to be highlighted to engage researchers and clinicians towards this new and exciting area of bio-nanoscience. We believe that these recent developments will offer researchers an updated source for the use of nanomaterials as an advanced approach to improve wound healing.
Keywords: Wound healing